1996
DOI: 10.1007/bf03011255
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia after otoplasty: regional nerve blockade vs local anaesthetic infiltration of the ear

Abstract: O,5,10,15, 30, 45 min with Recovery Room, and at O, 30, 60, 90, 120, 180, 240, 360, 480 min on the ward. Pain score >6 was treated with fentanyl I lag.kg -I iv (recovery) and morphine 0.2 mg.kg -I On or mefenamic acid 8 rag. kg -t po on the ward. Time to first supplemental analgesia was noted. Mean duration o.f analgesia was Group B (P > 0.7). 24% per cent of children (Group A) and 27% (Group B) required no supplemental analgesia (P > 0.6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In children, the axillary block is one of the most popular approaches to the brachial plexus (Cregg et al, 1996). Due to the abundance of vessels in the axillary region, caution must be taken when performing this block to avoid intravascular injection.…”
Section: Outcome and Discussionmentioning
confidence: 99%
“…In children, the axillary block is one of the most popular approaches to the brachial plexus (Cregg et al, 1996). Due to the abundance of vessels in the axillary region, caution must be taken when performing this block to avoid intravascular injection.…”
Section: Outcome and Discussionmentioning
confidence: 99%
“…The conventional approach for great auricular nerve blockade is a landmark-based technique, where the injection point is determined by drawing lines between the superior margin of the cricoid cartilage and the posterior border of the sternocleidomastoid muscle, with local anaesthetic subcutaneously injected at the intersection [5,8,9]. Interestingly, most descriptions of great auricular nerve blockade are in Table 1 Analysis of blocked areas (indicated by 'X') in each individual volunteer.…”
Section: Discussionmentioning
confidence: 99%
“…Seven different sensory distribution patterns have been observed 10 min after blockade of the great auricular nerve. children [5,[7][8][9]15], whereas only a few cases are reported in adults [14]. Ultrasound guidance enables selective blockade of small nerve structures with minimal volumes of local anaesthetic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Bilateral superficial cervical plexus block may also reduce postoperative analgesic requirements in children undergoing ear surgery. 4,5 A review of our experience with cochlear implantation identified a greater postoperative opioid consumption in children undergoing bilateral simultaneous cochlear implantation (BSiCI) when compared with children undergoing unilateral implants, and a suspicion arose that the greater analgesic requirement was a reflection of increased postoperative pain. 6 In an effort to decrease the discomfort related to the implant site and possibly decrease postoperative opioid requirements, intraoperative BSCPB was recently adopted and applied to all our children undergoing general anesthesia for BSiCI.…”
Section: Résumémentioning
confidence: 99%